Weed dynamics and critical period of crop weed competition in cumin (Cuminum cyminum) under arid region of Rajasthan - A Saxena, R Singh, (Journal of Spices and Aromatic Crops, 2013)
A field experiment was conducted to assess the effect of crop weed competition on yield and monetary benefit in cumin under arid conditions of Rajasthan. In the first year of the study Heliotropium oralifolium was the most dominating weed species with a relative density, relative frequency and importance value index (IVI) of 24.7, 23.5 and 48.2, respectively, while Chenopodium murale dominated during second year with a relative density, relative frequency and importance value index (IVI) of 47.8, 21.8 and 69.6, respectively. Weed competition index decreased with increasing weed free check period. However, weed competition index in weed free check maintained from 30 to 60 days after sowing (DAS) varied from 10.52 and 5.26, while it was 44.76 under weed free check up to 15 DAS. No significant difference in the growth, yield attributes and seed yield was recorded in weed free condition maintained beyond 30 DAS, but differed significantly over weed free check up to 15 DAS. Allowing weeds to compete with crop after 30 DAS and up to harvest significantly reduced yield attributes and seed yield compared to weedy check up to 15 DAS. The highest mean seed yield (437 kg ha-1) was recorded in season long weed free check, but net monetary benefit was highest (Rs. 19,520 ha-1) with weed free check up to 30 DAS. Thus, the crop should be weed free for at least initial 30 DAS.